Analisis Nilai Tambah Olahan Dodol Salak Di Desa Tamarenja Kabupaten Donggala - Ni Kade Widiani; Max Nur Alam; Abdul Muis (Universitas Tadulako, 2017)
This research aims to analyzed incomes and value added of Processed Dodol Salak in Tamarenja Village Donggala Regency, as one of the alternatives to reduce production losses thorny palm as a result of damage at the time of the storage period is done. This research is a qualitative descriptive. The population in this research is the home industry of processed dodol salak in the village Tamarenja Donggala Regency that the research sample, so that the method used census methods. Analyzed using analysis of income and value added. Results of this research is that the net income (profit) of processed home industry dodol salak Rp 1,142,575 per four times the production process for a month and added value obtained by Business Group from home industry business is Rp 32 815 per kilograms of raw materials used. Therefore the domestic industry of processed dodol salak in Tamarenja Village Donggala Regency conducted by KUB Jami'tun Khaerat can increase income and add value